MAXIMS OF POLITENESS PRINCIPLES IN ALICE THROUGH THE LOOKING GLASS MOVIE - Trisnaningtyas, Adelle; Budiwaty, Suci (UG Journal, 2021)
Politeness is a basic human behavior to build a harmonious relationship. This research discussed the maxims of the politeness principle that were found in a movie named ‘Alice Through the Looking Glass. The aims of this research were to find out that the maxims of the politeness principle that were used by the characters in ‘Alice Through the Looking Glass’ movie based on Leech’s theory. The method for this research was the qualitative method. This research used the movie script as the source of data. The result of this research showed that there are six maxims of politeness principles that were found in the movie, they are Tact Maxim with 6 data, Generosity Maxim with 7 data, Approbation Maxim with 5 data, Modesty Maxim with 5 data, Agreement Maxim with 5 data and Sympathy Maxim with 5 data. Generosity Maxim is the most dominant maxim that was used by the characters. Furthermore, this research can be concluded that the characters tend to be generous to show their politeness to one another.